Urolithiasis Basic Science and Clinical Practice - Talati, Jamsheer J.; Talati, Jamsheer J.; Tiselius, Hans-Goran.; Tiselius, Hans-Goran.; Albala, David M.; Albala, David M.; YE, ZHANGQUN.; YE, ZHANGQUN. (Springer London : Imprint: Springer, 2012)
Urolithiasis: Basic Science and Clinical Practice is a comprehensive text that assists urologists in defining the best choice of treatment for each case through a balanced presentation of underlying science, diagnostic methods and practical tips, with additional discussions on educational issues, costs and management of resources.   This user-friendly practical resource is replete with full-color illustrations and radiographs, covering all aspects of stone disease, and offering perspectives from Europe, the Americas, China, South Asia, Africa, and Australia. Topics include the biochemical and physiological basis of stone formation, treatment options, complications, assessment of techniques and technologies available, and guidelines on the prevention of stone recurrence.    Urolithiasis: Basic Science and Clinical Practice is the definitive text on stone disease and is a must read for young consultants starting a new practice, and urologists in residence and training.